2009
DOI: 10.1007/s10792-009-9314-y
|View full text |Cite
|
Sign up to set email alerts
|

Mitomycin C in the treatment of a Schneiderian (inverted) papilloma of the lacrimal sac

Abstract: Schneiderian papillomas are benign tumours, with an aggressive nature. A case with a recurrent Schneiderian papilloma of the nasolacrimal sac, who underwent an external dacryocystorhinostomy (DCR) with irrigation of the nasolacrimal system with 0.02% mitomycin C (MMC), is presented at 18 months follow-up. External DCR using MMC, as an adjuvant therapy, is a novel approach to the treatment of Schneiderian papilloma of the nasolacrimal tract. It allows preservation of function, compared with the conventional tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Mitomycin C was tried as an adjuvant therapy for dacryocystorhinostomy (DCR) approach in the treatment of Schneiderian papilloma of the nasolacrimal tract, and it showed preservation of function, compared with the conventional treatment of dacryocystectomy alone [336]. …”
Section: Treatmentmentioning
confidence: 99%
“…Mitomycin C was tried as an adjuvant therapy for dacryocystorhinostomy (DCR) approach in the treatment of Schneiderian papilloma of the nasolacrimal tract, and it showed preservation of function, compared with the conventional treatment of dacryocystectomy alone [336]. …”
Section: Treatmentmentioning
confidence: 99%
“…It allows preservation of function, compared with the conventional treatment of dacryocystectomy. 16 Jasna But-Hazdic et al did a study to evaluate the role of radiotherapy in patients who had inverted papilloma and SCC. They concluded that combination of surgery and postoperative radiotherapy dose levels in a range used for invasive SCC are recommended for operable disease.…”
Section: Resultsmentioning
confidence: 99%
“…This compares favorably with nasal and paranasal sinus IPs where the recurrence rates are reported to be 10-34%. [8] CONCLUSION Primary IPs of the lacrimal sac is a rare disease with only a handful of reported cases; orbital extension is extremely rare. We recommend enbloc resection of orbital and nasolacrimal part parts of the tumor with clear margins to avoid the need of adjuvant therapy.…”
Section: Discussionmentioning
confidence: 97%
“…Open approach is preferred as it provides adequate exposure for the orbital extension of the tumorand the periorbita, as well as allowing enbloc excision of the nasolacrimal canal via the medial maxillectomy. In view of high rate of recurrence (10-34%) and possibility of malignant transformation (5-11.5%), [8] complete resection of tumor with clear margins is mandatory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation